2006
DOI: 10.1021/bi0511639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Benzo[a]pyrene-2‘-deoxyguanosine Lesions On Methylation Of DNA by SssI and HhaI DNA Methyltransferases

Abstract: DNA damage caused by the binding of the tumorigen 7R,8S-diol 9S,10R-epoxide (B[a]PDE), a metabolite of bezo[a]pyrene, to guanine in CpG dinucleotide sequences could affect DNA methylation and, thus, represent a potential epigenetic mechanism of chemical carcinogenesis. In this work, we investigated the impact of stereoisomeric (+)- and (-)-trans-anti-B[a]P-N(2)-dG adducts (B(+) and B(-)) on DNA methylation by prokaryotic DNA methyltransferases M.SssI and M.HhaI. These two methyltransferases recognize CpG and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 83 publications
1
43
0
Order By: Relevance
“…The impact of (+)- and (-)- trans -B[ a ]PDE- N 2 -dG adducts and (+)- cis -B[ a ]PDE- N 2 -dG adduct on methylation of 18-mer DNA duplexes by M.SssI was studied earlier [7, 8]. However, in the present work, we focused on the impact of two types of intercalative adducts that were not examined before.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The impact of (+)- and (-)- trans -B[ a ]PDE- N 2 -dG adducts and (+)- cis -B[ a ]PDE- N 2 -dG adduct on methylation of 18-mer DNA duplexes by M.SssI was studied earlier [7, 8]. However, in the present work, we focused on the impact of two types of intercalative adducts that were not examined before.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA substrates contained overlapping recognition sites of M.HhaI (5′-GCGC), M.SssI (5′-CG) and Dnmt3a (5′-CG). It was shown that the MTase binding affinities for 18-mer canonical DNA and 18-mer (+)- and (-)- trans -B[ a ]PDE-DNA decrease in the order M.HhaI > M.SssI > Dnmt3a-CD, with K d values in the range 10 pM – 70 nM [7, 8, 14]. The enhancement of fluorescence intensities (I 384 ) by a factor 45-50 relative to protein-free B[ a ]PDE-DNA duplexes was observed in the case of G C G t+ C/C GM G•М.SssI•AdoHcy, G t+ C G C/C GM G•M.HhaI•AdoHcy, and G C G t+ C/C GM G•M.HhaI•AdoHcy complexes with (+)- trans -B[ a ]PDE -N 2 -dG adducts positioned within the MTase recognition sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, disposition of Hoechst 33258 in the DNA minor groove was demonstrated for type I and II complexes with poly(dGdC)·poly(dG-dC) 28 . Recently we found that the presence of a bulky benzo[a]pyrene residue in the DNA minor groove caused a dramatic decrease in prokaryotic MTases SssI and HhaI methylating capacity because of distortion of DNA contacts with the enzyme catalytic loop 29,30 . Superimposition of the DNA methyltransferase HhaI (M.HhaI-DNA) complex structure onto the Dnmt3a-CD structure showed high similarity of M.HhaI and Dnmt3a-CD catalytic loop conformations 7 .…”
Section: Resultsmentioning
confidence: 99%